1970
DOI: 10.4314/ejhs.v28i5.4
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Malaria in Tselemti Wereda, North Ethiopia: A Retrospective Study

Abstract: BACKGROUND: A significant segment of the world’s population is at risk of contracting malaria infection at any one time. In Ethiopia, sustained control efforts have been made in the past decade to fight malaria. Yet, it remains as the major cause of morbidity, mortality and socioeconomic problems in the country. The intensified control of malaria can further be augmented by analyzing health facility based malaria data. Hence, the aim of this study was to determine the magnitude of malaria infection in Northwes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
12
3
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 9 publications
9
12
3
1
Order By: Relevance
“…The dominant Plasmodium species detected in the current study participants was P. falciparum . This finding is congruent with national figures and other similar studies in parts of Ethiopia that reported preponderance of P. falciparum than P. vivax [ 3 , 8 , 26 , 27 ]. However, this is incongruity with the previous report from Jimma Town, which reported a higher prevalence of P. vivax than P. falciparum [ 28 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The dominant Plasmodium species detected in the current study participants was P. falciparum . This finding is congruent with national figures and other similar studies in parts of Ethiopia that reported preponderance of P. falciparum than P. vivax [ 3 , 8 , 26 , 27 ]. However, this is incongruity with the previous report from Jimma Town, which reported a higher prevalence of P. vivax than P. falciparum [ 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, more males (55.4%) were affected by malaria than females (44.6%). This finding is concurrent with studies from several localities in Ethiopia that reported higher malaria burden among males than females [ 23 , 26 , 27 ]. The higher prevalence rate in males might be due to the fact that males are usually engaged in outdoor activities at dusks and dawns, coinciding with the peak biting hours of the exophagic mosquito species.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar trend of Plasmodium parasite distributions were reported from Gilgel-Gibe [31] and children from Northern Ethiopia [32] and migrant laborers from North-western Ethiopia [33]. Retrospective studies from Kola Diba health centre [22], Serbo health centre [23], Metema hospital [24], Kombolcha [25], and Tselemti Woreda [34] and a survey from different part of Ethiopia [35] also support this study nding. However, reports showed that P. vivax was the dominant species in some part of Ethiopia [28, 36, & 37].…”
Section: Discussionsupporting
confidence: 86%
“…Une prévalence qui devrait être plus importante si l'étude a été menée en saison pluvieuse, période de forte endémie palustre. Ramdzan et al (2020) en Indonésie et Meresa et al (2018) en Ethiopie ont rapporté des prévalences similaires respectivement 33,6% et 45,3% en population. Une prévalence plus élevée a été rapportée par Tusting et al (2017) au Burkina Faso notamment 70,6% à l'examen microscopique et 79,8% au test diagnostic rapide.…”
Section: Discussionunclassified